Corporate Governance and Strategic Management Accounting Disclosure - Setianingtyas Honggowati; Rahmawati Rahmawati; Y. Anni Aryani; Agung Nur Probohudono (Universitas Pasundan, 2017)
The aim of this study is to examine the corporate governance influence on strategic management accounting disclosure. The strategic management accounting disclosure in this study was measured by the disclosure level regarding strategic management accounting published in the company's annual report according to the index (made by the author). The corporate governance is proxied by board size, independent board, and managerial ownership. The data of this study are 497 manufacturing companies in Indonesia in the period of 2011-2015 and the method employed in this study is regression analysis method. The findings show that board size has significant positive influence on the disclosure level of strategic management accounting of manufacturing companies in Indonesia, and the proportion of independent board does not influence SMA disclosure, while managerial ownership has negative influence the disclosure level of strategic management accounting.